2011
DOI: 10.1111/j.1365-3059.2011.02511.x
|View full text |Cite
|
Sign up to set email alerts
|

SSR marker analysis of Monilinia fructicola from Swiss apricots suggests introduction of the pathogen from neighbouring countries and the United States

Abstract: Monilinia fructicola is a quarantine fungal pathogen in Europe, but many major stone fruit growing countries in Europe have reported its presence recently. In Switzerland, the fungus was first found in a single apricot orchard in 2008. This study confirms the presence of M. fructicola in nine out of 22 commercial orchards in Canton Valais, Switzerland. Five simple sequence repeat markers (SSRs) were developed for M. fructicola and samples from Switzerland, Spain, Italy, France and the United States were analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Villarino et al (2012) found genetic differences among isolates of M. fructicola from French and Spanish orchards. Similar result was also reported by Jänsch et al (2012) with M. fructicola isolates from the United States and Europe. For these authors, the variability among isolates may have occurred due to sexual reproduction, accumulation of random mutations or through gene flow.…”
Section: Isolatessupporting
confidence: 79%
“…Villarino et al (2012) found genetic differences among isolates of M. fructicola from French and Spanish orchards. Similar result was also reported by Jänsch et al (2012) with M. fructicola isolates from the United States and Europe. For these authors, the variability among isolates may have occurred due to sexual reproduction, accumulation of random mutations or through gene flow.…”
Section: Isolatessupporting
confidence: 79%
“…Hence, Monilinia isolates could be grown on PDA Petri dishes directly from infected organs, i.e., fruits, mummies, twigs [193], or already prepared cultures. In addition, there are numerous methodologies describing partially similar, and in some cases divergent, protocols concerning spores concentration, inoculum load, and associated variables for screening BR susceptibility in stone fruits, peach and nectarine in particular.…”
Section: Procedures For Spore Production and Inoculation In Lieu Of Bmentioning
confidence: 99%
“…The sequences of the flanking markers were blasted against the 'Golden Delicious' genomic sequence (Velasco et al 2010) using BLAST (Altschul et al 1990), and SSR repeats were identified using the microsatellite finder webtool ''YourLabData'' (2011). SSR-specific primers were designed using the Primer 3 webtool v.0.4.0 (Rozen and Skaletsky 2000), labeled primers were purchased from Microsynth AG (Balgach, Switzerland), and the SSR marker analysis conducted according to Jänsch et al (2012). The parents of the cross and a total of 10-25 resistant and susceptible progeny plants as well as recombinants around the resistance locus (4-11 genotypes) were screened to identify and map the SSR markers that were polymorphic in the resistant parent.…”
Section: Plant Materials and Dna Extractionmentioning
confidence: 99%